Towards a Dialogical Decolonised Psychotherapy - Leopeng, Bandile (PINS-Psychology in Society, 2019)
In the following article I will argue for a new type of therapeutic approach which I have termed “dialogical decolonised psychotherapy”, which uses similar concepts that are the foundation of Freire’s Pedagogy of Freedom (2000) and Martín-Baró’s liberation psychology (1996), and applies them to contemporary psychotherapy in South Africa. This article focuses on the practice of psychotherapy in public and private settings. In line with this, the existing models of psychotherapy which utilise exclusively westernised frameworks by practising clinicians are regarded as potentially damaging to the therapeutic relationship in South Africa. I introduce “Therapy as Dialogical” and show how this approach is preferable in terms of building a genuine therapeutic relationship where all clients and psychotherapists are considered participants in creation.